2015
DOI: 10.1002/cpp.1991
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in Life in People with Borderline Personality Disorder

Abstract: The results of this study suggest that meaning in life is a relevant variable in the psychopathology of BPD The results of this study suggest that meaning in life is associated with non-suicide self injuries This study suggests that current therapies for BPD should focus on increasing the meaning in life in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
2
32
0
1
Order By: Relevance
“…Studies with participants diagnosed with BPD (Marco et al, 2015a) found that meaning in life was highly and negatively correlated with the main symptoms of BPD.…”
mentioning
confidence: 99%
“…Studies with participants diagnosed with BPD (Marco et al, 2015a) found that meaning in life was highly and negatively correlated with the main symptoms of BPD.…”
mentioning
confidence: 99%
“…It was found that low meaning in life was a characteristic of people diagnosed with borderline personality disorder (PD). This group presented with a greater sense of emptiness, identity disturbance and confusion …”
Section: Introductionmentioning
confidence: 95%
“…This group presented with a greater sense of emptiness, identity disturbance and confusion. 15 Frankl 1 emphasized the importance of purposefulness and meaningful goal direction as a motivating force in mature people. Cloninger used goal direction: the identification of individually valued goals and purposes as part of his definition of self-directedness.…”
Section: Introductionmentioning
confidence: 99%
“…To assess PWB, six core dimensions are widely used: self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth 10 . Several studies have found that people who believe their lives have meaning or purpose appear better off, with better mental and physical health and engagement in healthier life styles [11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%